Synthesis of hyaluronic acid hydrogels using click chemistry approach for biomedical applications - Gupta, N.; Tiwari, N.; Badiger, M. (Trends in carbohydrate research, 2018)
Hyaluronic acid (HA) is one of the most versatile biomaterial which forms an essential component of an extracellular matrix (ECM) and plays a vital role in wide variety of biological processes. Inherent biocompatibility, biodegradability and presence of functional groups for modification make it an attractive material for the synthesis of hydrogels for biological applications. In the present work, we have explored an azide-alkyne click chemistry approach for the preparation of HA hydrogels. Furthermore, we incorporated the hydrolysable carbonate ester linkages which are known to cleave in the physiological environment. The hydrogels with carbonate ester linkages and incubated with drug molecules can be used for the slow release of drug molecules. The hydrogels synthesized using azide alkyne click chemistry was characterized using NMR and IR spectroscopy.